Seismic analysis of PWR control rod drop with the CRDAC scram performance code. (April 2018) - Huang, Heng; Wang, Zhanwei; Xu, Wei; Liu, Tong; Yang, Yiren; Li, Peng
Highlights: A new control rod dropping model considering the effect of the fluid-induced lateral motion of the rod is developed in this paper. A new computation codes, namely CRDAC, were obtained, and the accuracy of which is verified by using the in-house code. CRDAC provides a wider scope analysis, specifically in two seismic load input forms and arbitrary initial fuel assembly shape. The influence of different levels earthquake and initial shape of fuel assembly on the response and key parameter were discussed. Abstract: In a pressurized water reactor (PWR), the control rod drop analysis is crucial for the reactor safety and the integrity of core structure. Especially under a seismic condition, the horizontal deflections of the reactor system could cause impact between the control rods and the guide thimbles, and then the resulting frictional forces can significantly increase the scram time and intensify mechanical interaction at the absorber rod cladding and spider springs. The CRDAC code is a control rod scram analysis tool developed by China Nuclear Power Technology Research Institute (CNPRI). In a previous work, Liu et al. (2013), Li et al. (2013) studied the transverse behavior and the fluid-structure interaction of the whole movement system based on this code. Liu calculated the scram time of a 12ft fuel assembly under the Wenchuan earthquake wave.Huang et al. (2014) proposed a flow model to describe the effect of the flow field parameters on the scram time under the operation condition. This paper presents the seismic analysis method based on the CRDAC code which developed by China Nuclear Power Technology Research Institute (CNPRI). Both the scram time and the seismic response have been calculated, such as the maximum pressure in the guide thimble, impact forces to the spider spring, and friction forces to the absorber rod. According to the design requirements of the third-generation nuclear power plants, safety shutdown earthquake (SSE) and operating basis earthquake (OBE) for the horizontal response need to satisfy 0.3 g and 0.15 g, respectively. Therefore, the maximum accelerations of both the input and the initial horizontal deformation of a fuel assembly have been taken into account in this paper. After several sensitive analyses, it is found that the CRDAC code is a powerful tool for the design of control rods and fuel assemblies.